ANALISIS MAKNA TEMBANG DOLANAN LIR-ILIR MELALUI PENDEKATAN SEMIOTIK PADA KAJIAN BAHASA JAWA - Selvia Eva Novaliana; Bagus Wahyu Setyawan (Jurnal Komunikasi dan Budaya, 2023)
Islam is the religion of rahmatan lil alamin or that which is divine for all of nature. The values contained in Islam have a very broad scope relating to various aspects of life. The spread of Islam in Java is growing rapidly brought by Walisongo, or what is called the nine Wali. One of the trustees who uses a unique preaching media is Sunan Kalijaga. He creates lir-ilir song, which without realizing it in this song, has a very meaningful meaning in life. The meaning in it awakens the Javanse people to always think about carrying out the pillars of Islam, and to improve themselves if they make mistakes. However, not everyone knows the meaning contained in the lir-ilir song. In this study, the overall meaning of the song lir-ilir will be examined using a semiotic approach. The semiotic approach here relates to the system of signs and symbols in human life.